2016
DOI: 10.1177/1467358416637252
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delays and cancellations on travel from small community airports

Abstract: Commercial air service is important to residents and tourists in small communities, but small communities have seen a reduction (and sometimes elimination) of commercial air service. Anecdotal evidence suggests that flight interruptions (delays and cancellations) negatively impact these airports, as local residents drive to nearby hubs instead of flying from the local airport. This study looks at the impact of delays and cancellations by considering their effect on an entire travel itinerary. This study invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(31 reference statements)
1
3
0
4
Order By: Relevance
“…The problem is especially notable at large airports, as well as at regional airports with seasonal character, inadequate operating management system, and limited capacities of single subsystems. The study [24] assesses the impact of delays and cancellations by considering their effect on the entire travel itinerary. The research considers the influence of regional flights (flight between a regional airport and hub airport) on the entire trip.…”
Section: Regional Airports' Traffic Sharementioning
confidence: 99%
“…The problem is especially notable at large airports, as well as at regional airports with seasonal character, inadequate operating management system, and limited capacities of single subsystems. The study [24] assesses the impact of delays and cancellations by considering their effect on the entire travel itinerary. The research considers the influence of regional flights (flight between a regional airport and hub airport) on the entire trip.…”
Section: Regional Airports' Traffic Sharementioning
confidence: 99%
“…Os roteiros turísticos têm sido estudados em duas grandes abordagens. Na primeira abordagem, tais roteiros são tratados como mapas prescritos a ser seguidos, e os estudos buscam compreender relações entre determinadas variáveis com influências sobre os roteiros (Li, Zhou & Zhao, 2016;Stone, 2016). Na segunda, os roteiros são tratados como rotas experienciais, em estudos com maior foco no caráter epistemológico do turismo (Cisne & Gastal, 2011).…”
Section: Introductionunclassified
“…Essa visão se opõe aos estudos que tratam os processos organizacionais ligados ao turismo como algo previsível (Li et al, 2016;Stone, 2016), ignorando aspectos relevantes da sua dinâmica -por exemplo, a extensão na qual, mesmo quando planejado antecipadamente, "[...] o pacote ou roteiro turístico possui inúmeras situações imprevisíveis, pois as preferências e decisões de consumo se manifestam à medida que a viagem se desenvolve [...]" (Tomazzoni et al, 2008, p. 145).…”
Section: Introductionunclassified
“…The authors Jiang and Ren (2018) propose a model that can effectively describe the behaviour of passengers at various delays. The author Stone (2018) found that flight delays or cancellations have a negative impact, especially on passengers at small airports (locals and tourists), who then have to travel to the transfer airport instead of departing from these small airports. This further increases the impact of these passengers on the entire travel itinerary.…”
Section: Introductionmentioning
confidence: 99%